Pengaruh Kinerja Keuangan Terhadap Nilai Perusahaan Dengan Kebijakan Deviden Sebagai Variabel Moderasi : Studi Pada Perusahaan Sektor Makan Minum yang Terdaftar Di Bursa Efek Indonesia Tahun 2018-2022 - Margareta Verna Lusi Yenianse (Yayasan Literasi Ilmiah Indonesia, 2024)
Purpose: This research aims to prove the influence of financial performance on company value with dividend policy as a moderating variable (study of food and drink sector companies listed on the Indonesian Stock Exchange in 2018-2022). Methodology: The approach used in this research is a quantitative approach. The research took samples from all food and drink companies listed on the Indonesia Stock Exchange, companies in the food and drink sector, for example companies that provide the most complete information related to research and companies that present data in rupiah. Secondary data was obtained from food and drink sector companies listed on the Indonesian Stock Exchange in 2018-2022 and then processed using SPSS with descriptive analysis techniques. Findings: The research results show that profitability and liquidity have a significant positive influence on company value Novelty: researchers added accounting knowledge as a moderating variable to find out whether accounting knowledge can make other factors such as financial performance, company value and dividend policy have a positive or negative influence on company value. Key words: profitability, liquidity, company value and dividend policy.